Colombia : Third Review Under the Stand-By Arrangement and Request for a Waiver of Nonobservance of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2004)
This paper discusses Colombia Third Review Under the Stand-By Arrangement (SBA) and Request for Waiver of Nonobservance of Performance Criterion. Under the authorities' program, economic performance has improved considerably. Real GDP rose by 3.7 percent in 2003 and 3.8 percent in the first quarter of 2004, while inflation fell to 5.4 percent year over year in May, lower than expected. Solid export growth, together with improved confidence, has strengthened the external position. Fiscal policy is on track, and almost all structural reforms continue to advance.